Visoki ileus, povzročen z žolčnim kamnom (Bouveretov sindrom) - Golobinek, Rajko (Zdravniški vestnik, 2006)
Background Mechanical ileus caused by gallstones (Bouveret syndrome) is late complication of cholelithiasis. Chronical irritation and recurrent conservativelly treated episodes of acute cholecystitis lead to weakening of gallblader wall and formation of internal biliar fistula (predominantly into duodenum). Gallstones migration through the fistula cams cause intestinal obstruction, which requires surgical treatment. Patients and methods A case ofa 78-years old female patient with high ileus is presented. Preoperative examinations (endoscopy, gastroduodenography, abdominal ultrasound, CT scan and histology) suggested duodenal obstruction due to translocated and impactedgallstone - Bouveret syndrome. Intraoperativelly this diagnosis was confirmed, gallstone removed and cholecystectomy and the cholecystoduodenal fistula repair was made. Conclusions The Bouverets yndrome is a rare cause of mechanical ileus. It is presented in aged patients as late complication of gallstones and demands operative treatment. Desobstruction is mandatory, according to patient's general condition cholecystectomy and fistula repair are strongly recomended.
Keywords: Aged; Cholecystectomy; Cholelithiasis; Črevesna obstrukcija; Holecistektomija; Intestinal Obstruction; kirurško zdravljenje; Starostniki; Surgery; therapy; zapleti; zdravljenje; Žolčni kamni